Rare bird documentation form for Glaucous Gull at Saylorville Reservoir, 1988 - Dinsmore, Stephen J.et al (1988)
Rare bird documentation form for a Glaucous Gull at Saylorville Reservoir in Polk County, IA on November 30, 1988. Epson - sheet feed